A note on the correct spelling of the name of the freshwater shrimp Macrobrachium olfersii (Wiegmann, 1836) (Decapoda, Palaemonidae) - Rossi, Natália; Grave, Sammy De; Mantelatto, Fernando L. (Zootaxa, 2016)
Macrobrachium olfersii (Wiegmann, 1836), popularly known as Pitu, Bristled River Shrimp and Buchura River Prawn, is a freshwater shrimp species widespread along the eastern coasts of the Americas. The species can be found from the southeastern United States, where the prawns were introduced (Holthuis & Provenzano, 1970), southwards to Rio Grande do Sul (Brazil), including numerous records in Mexico, Nicaragua, Costa Rica, Panama, Colombia, Venezuela, Guyana and Suriname (Holthuis, 1952; Williams, 1984; Melo, 2003; Valencia & Campos, 2007).